2005
DOI: 10.1111/j.1475-6773.2005.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Physician Visits, Hospitalizations, and Socioeconomic Status: Ambulatory Care Sensitive Conditions in a Canadian Setting

Abstract: In the Canadian universal health care plan, the poor have reasonable access to ambulatory care for ACS conditions. Ambulatory care may be more effective in preventing hospitalizations among relatively affluent individuals than among the less well off.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
177
2
19

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(207 citation statements)
references
References 50 publications
9
177
2
19
Order By: Relevance
“…Our finding that very high neighborhood poverty is associated with higher preventable hospitalization rates builds on Billings and colleagues' analysis of New York City hospitalizations 20 years ago (1982 to 1993), although they found the disparity between low-income and high-income neighborhoods increased during that time period. 1 Studies in countries with universal health coverage have also found that preventable hospitalizations are higher for low-income populations and residents living in lowincome neighborhoods, 37,38 suggesting that quality and availability of primary care may be an issue for people living in high poverty neighborhoods regardless of insurance status. In New York City, every very high poverty neighborhood also qualifies as a federally designed Health Professional Shortage Area or Medically Underserved Area in whole or in part, indicating that these areas or populations have a shortage of primary medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that very high neighborhood poverty is associated with higher preventable hospitalization rates builds on Billings and colleagues' analysis of New York City hospitalizations 20 years ago (1982 to 1993), although they found the disparity between low-income and high-income neighborhoods increased during that time period. 1 Studies in countries with universal health coverage have also found that preventable hospitalizations are higher for low-income populations and residents living in lowincome neighborhoods, 37,38 suggesting that quality and availability of primary care may be an issue for people living in high poverty neighborhoods regardless of insurance status. In New York City, every very high poverty neighborhood also qualifies as a federally designed Health Professional Shortage Area or Medically Underserved Area in whole or in part, indicating that these areas or populations have a shortage of primary medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Sabe-se que piores condições socioeconô-micas afetam o acesso aos serviços de saúde, modificam o padrão de utilização desses, dando preferência ao uso de serviços de emergência, prejudicam a adesão ao tratamento (falta de dinheiro para comprar medicamentos), dificultam a adoção de hábitos saudáveis e o amparo da rede de suporte social. Estudos prévios enfatizaram a importância desses fatores e apontam para maiores taxas de ICSAP entre a população de piores condições socioeconômicas 7,8,20 .…”
Section: Discussionunclassified
“…However, the reducing number of hospitalizations can also be a result of the insufficient number of beds and barriers in hospital access 27 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, when health care is performed by services who do not work with the FHS, there is significant increase in hospitalization rates for ACSC 4 . The longitudinal aspect of care provided by FHS professionals and the connection between users and workers contribute with the increasing resoluteness and with the reduction of hospitalizations 13,27 .…”
Section: Discussionmentioning
confidence: 99%